Questions of geopolitical space formation - Chukubayev, E. S.; Yechshanov, I. (International relations and international law Journal, 2016)
The contemporary understanding of geopolitics and its main factors have a little different character rather than earlier. The geopolitics is understood as a science about laws of distribution and redistribution of spheres of influence (the Force Centers) various states and interstate associations in multidimensional communication space. In the end of the last century the newest geopolitics overcoming narrowness of traditional and new geopolitics with the dominating geographical or economic determinism has started to be formed. The newest geopolitics operates with the Big spaces of a multidimensional associativity. Great and regional powers aspire to create effective geopolitical space, but not it is possible to all. An important basis of the modern geopolitical forecast is the understanding and development geostrategy in relation to formation of the protected geopolitical space. In connection with the difficult and inconsistent